2023
DOI: 10.1136/bmjopen-2023-072061
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Acceptance and Commitment Therapy programme on HbA1c, self-management and psychosocial factors in adults with type 1 diabetes and elevated HbA1c levels: a randomised controlled trial

Ingrid Wijk,
Susanne Amsberg,
Unn-Britt Johansson
et al.

Abstract: ObjectiveTo evaluate the impact of an Acceptance and Commitment Therapy (ACT) programme, tailored for people living with type 1 diabetes, on glycated haemoglobin (HbA1c), self-management and psychosocial factors among individuals with HbA1c>60 mmol/mol compared with treatment as usual (TAU).SettingAn endocrinologic clinic in Sweden.ParticipantsIn this randomised controlled trial, 81 individuals with type 1 diabetes, aged 18–70 years with HbA1c>60 mmol/mol, were randomly assigned to either an ACT group in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(155 reference statements)
0
1
0
Order By: Relevance
“…Makine et al reported that patients with high depression scores were less accepting of insulin treatment than those with low depression scores [19]. Wijk et al [20] showed that an intervention program for factors such as depression, anxiety and general stress increased insulin treatment acceptance and adherence to treatment. Considering the current study data and previous literature, we recommend that depression and anxiety should be evaluated before starting insulin therapy in individuals without a diagnosis of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Makine et al reported that patients with high depression scores were less accepting of insulin treatment than those with low depression scores [19]. Wijk et al [20] showed that an intervention program for factors such as depression, anxiety and general stress increased insulin treatment acceptance and adherence to treatment. Considering the current study data and previous literature, we recommend that depression and anxiety should be evaluated before starting insulin therapy in individuals without a diagnosis of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%